Maternal Hemodynamic and Nutritional Determinants of Neonatal Apgar score: The Role of Gestational Age, Body Mass Index, Hemoglobin, and Mean Arterial Pressure - Sumarni Sumarni; Dyah Puji Astuti; Siti Mutoharoh; Diah Astutiningrum; Fitria Prabandari (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2026)
Background: The Apgar score is widely used to evaluate a newborn's physiological adaptation during the early transition from fetal to extrauterine life. Maternal physiological and nutritional conditions during pregnancy may influence neonatal outcomes. This study investigated the association between maternal hemodynamic parameters, nutritional status, and neonatal Apgar scores. Method: A retrospective observational analytic study was performed using medical records from Margono Soekardjo Hospital collected in 2022. The study involved 190 mother–infant pairs selected through sequential sampling according to predetermined eligibility criteria. Gestational age, mean arterial pressure (MAP), hemoglobin concentration, and body mass index (BMI) were examined as independent variables, while the Apgar score served as the outcome variable. Statistical analyses included Spearman rank correlation and multiple linear regression, with statistical significance established at p < 0.05. Result: Gestational age demonstrated a significant moderate positive relationship with Apgar score (ρ = 0.549; p < 0.001), indicating that increasing gestational age was associated with better neonatal adaptation. In contrast, maternal BMI was weakly and inversely correlated with Apgar score (ρ = -0.329; p < 0.001). No significant associations were observed between Apgar score and either hemoglobin level (ρ = -0.016; p = 0.825) or MAP (ρ = -0.022; p = 0.765). Regression analysis further identified gestational age (β = 0.494; p < 0.001) and BMI (β = -0.167; p = 0.008) as significant predictors of Apgar score, whereas hemoglobin concentration and MAP did not contribute significantly to the model. Conclusion: Neonatal Apgar scores are primarily influenced by gestational age, with maternal BMI also showing a significant contribution. Conversely, maternal hemoglobin levels and mean arterial pressure were not associated with neonatal Apgar outcomes. These findings highlight the critical role of fetal maturity and maternal nutritional condition in supporting successful neonatal adaptation after birth